eorder the terms:
12 = -44 + 5x + -13x
Combine like terms: 5x + -13x = -8x
12 = -44 + -8x
Solving
12 = -44 + -8x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8x' to each side of the equation.
12 + 8x = -44 + -8x + 8x
Combine like terms: -8x + 8x = 0
12 + 8x = -44 + 0
12 + 8x = -44
Add '-12' to each side of the equation.
12 + -12 + 8x = -44 + -12
Combine like terms: 12 + -12 = 0
0 + 8x = -44 + -12
8x = -44 + -12
Combine like terms: -44 + -12 = -56
8x = -56
Divide each side by '8'.
x = -7
Simplifying
x = -7